The Queens Regnant of Navarre - Woodacre, Elena. author. aut Link
XXII, 267 p.
Keywords: The five queens of Navarre were the largest group of female sovereigns in one European realm during the Middle Ages, but they are largely unknown beyond a regional audience. This survey fills this scholarly lacuna, focusing particularly on issues of female succession, agency, and power-sharing dynamic between the queens and their male consorts.